Reclaiming the Abyss, Reckoning with Time: Water in the Afrofuturist Imagination - Patrizi, Chiara (Oltreoceano - Rivista sulle migrazioni, 2024)
Water is a powerful image in black diasporic literature, and a particularly evocative one for Afrofuturism, as testified by various contemporary Afrofuturist artworks, ranging from music to visual arts and literature. My essay focuses on two North American black authors, Nalo Hopkinson and Rivers Solomon, so as to analyze how their writings employ water imagery— and, specifically, imagery related to the Atlantic Ocean—to reclaim a sense of temporality and history that can truly mirror black experience and go beyond oppression and marginalization, in accordance to what Michelle M. Wright has theorized in her work Physics of Blackness (2015) and to what several Afrofuturist scholars have pointed out in the past few decades (Dery 1993; Eshun 2003; Nelson 2001; Lavender 2019) regarding science-fiction’s subversive potential for black expression. This reframing and acknowledgement of non-conforming black experiences/subjectivities is made possible also by the two authors’ reinterpretation of African water mythologies and deities, merfolk/mermaids in particular. In the novels examined, these creatures become the embodiment of a hybrid identity in which the past, the present, and the future converge in a creative way, dismantling traditional depictions of alterity and processes of othering. I will further argue that in Hopkinson and Solomon’s writings, as a source of both life and death, the oceanic waters constitute an environment which allows us to envision the possibility for a different future than that imposed by canonical Western notions, as well as contributing to the characters’ identity-building path. By plunging into the physical and symbolic abyss of the Atlantic Ocean, these novels retrieve a painful yet transfigured past, looking at it not as an enemy, but as an instrument of awareness and activism.